Analysis of Sodium Benzoate Content in Sauces Circulating in Segiri Market Samarinda City by UV-Vis Spectrophotometric Method - Jenly Adinata; Nurillahi Febria Leswana; Maria Elvina Tresia Butar-Butar (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Sodium benzoate is one of the permitted preservatives, if the amount is still below the maximum limit. This study was conducted to identify sodium benzoate levels in sauces circulating in Segiri Market, Samarinda. According to BPOM RI regulation No.36 of 2013, the maximum amount of sodium benzoate used in sauce is 1000 mg/kg. In this study, a qualitative analysis of sodium benzoate was carried out using the FeCl3 reagent, where 10 sauce samples taken from the Segiri market in Samarinda City were positive of containing sodium benzoate, forming a salmon-colored or brownish-red precipitate. Quantitative analysis was performed using a UV-Vis spectrophotometer where sodium benzoate was measured at a maximum wavelength of 226 nm. The verification parameters tested in this study are accuracy test and precision test. Based on the verification parameters, the average % recovery was 94.505% which is still in the range of 80-110%, and %RSD of 0.0642% which is less than 2%. Based on quantitative analysis, sample A content was 2,084.8 mg/kg, sample B was 1,895.1 mg/kg, sample C was 2,547.4 mg/kg, sample D was 1,700.7 mg/kg, sample E was 1,466 mg/kg, sample F was 7. 100.1 mg/kg, sample G by 1,388.1 mg/kg, sample H by 1,587.6 mg/kg, sample I by 1,647.1 mg/kg, sample J by 3,172.9 mg/kg, the sodium benzoate content in the sauce samples above the maximum amount as determined by the BPOM regulation No. 36 of 2013. Keywords: Sodium benzoate, Preservative, Sauce, UV-Vis Spectrophotometry